Pengaruh Kompetensi Profesional Guru Pendidikan Agama Islam Terhadap Hasil Belajar Peserta Didik Di SMA Al-Islam Krian Sidoarjo - Putra, Alek Wijaya (STAI Denpasar Bali, 2024)
The significant increase in learning outcomes for Islamic religious education is due to one factor, namely the professional competence of Islamic religious education teachers. This research aims to determine the competency of professional Islamic religious education teachers at Al-Islam Krian Sidoarjo High School, to determine the increase in student learning outcomes at Al-Islam Krian Sidoarjo High School, and to determine the influence of the competency of Islamic religious education professional teachers on improving participant learning outcomes. studied at Al-Islam Krian Sidoarjo High School. The method used in this research is a quantitative method with a product moment correlation approach. The population of this research is all students. The sample in this research is several students at SMA Al-Islam Krian Sidoarjo taken per class of 5-6 students. The X variable is the professional competence of Islamic religious education teachers and the Y variable is student learning outcomes. The data collection technique uses observation, questionnaires and documentation. Based on the data analysis carried out, the Professional Competency of Teachers at Al-Islam Krian Sidoarjo High School is running